National council of provinces rhetoric in overseeing the implementation of South Africa's national development plan - Mvulane, Sebolelo Constance (Department of Private Law, 2023)
This thesis is about analysing the political rhetoric of the National Council of Provinces (NCOP), in overseeing the implementation of South Africa's National Development Plan (NDP).1 The study seeks to define the underlying reasons which, compound slow policy implementation, particularly as exacerbated by weakened and misaligned policy oversight debates in the NCOP. This study is particularly important because the NDP is the long-term vision and development plan of the governing African National Congress's vision 2030. Findings from the National Planning Commission's Diagnostic Report which, was released in June 2011, indicated that “a failure to implement policies and an absence of broad partnerships have been identified as some of the main reasons for the slow progress in implementing the country's transformation policies.” 2 In addition to these prevailing conditions, “it is also imperative to note that South Africa had found itself in the middle of a technical recession and had still been grappling with the impact and aftermath of the Global Financial Crisis, at the time when the NDP was adopted in 2012. 3 ” “The global financial crisis had a dire impact on the South African labour market, resulting in the shedding of almost 1 million jobs over 2009 and 2010, reflecting longer term structural problems.”4 The NDP was hence developed in part, to address the impact of the 2008 global financial crisis, alongside growing and prevailing social and economic challenges in South Africa. Inherited inequalities had been exacerbated, in part by the fact that Parliament and particularly the NCOP, had not been able to adequately give full effect to its three sphere oversight role as underpinned by its cooperative governance and intergovernmental relations constitutional mandate. Consequently, this has led to an inability to meaningfully oversee and accelerate the implementation of South Africa's transformation policies. The study will place strategic focus on how the quality of arguments communicated in the NDP could either catalyse or impede the oversight and accountability work of the NCOP, thereby inadvertently decelerating the implementation of the NDP. The study also provides an overarching perspective of South Africa's broader rhetorical situation, which manifest as exogenous shocks within the NCOP's operating environment. The overarching rhetorical situation is also postulated as one of the key determinants, impacting how the NCOP approaches and shapes its policy debates. Specific emphasis will also be placed on the National Council of Provinces (NCOP) in the fifth parliament (particularly the 2015 appropriations budget vote process) and how the second chamber of Parliament has for purposes of executing its constitutional mandate of three sphere oversight and accountability, interpreted, synthesized, and as a result executed its oversight functions, based on the rhetoric of the NDP in relation to the outcomes in the NDP that focus on the economy, employment, and the NDP's commitment to building a capable developmental state. This study is of great importance and is necessitated by the imperative to ensure that the NCOP matures in its role as construct of South Africa's constitutional democracy, which is tasked with the important responsibility of undertaking three-sphere oversight to oversee the implementation of key development policy constructs and development catalysing legislation, as guided by the NDP.